Elaboración de una guía didáctica del área nacional de recreacional el boliche para el área de campismo y recreación del laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la UA-CAREN de la Universidad Técnica de Cotopaxi, (fase ii) - De La Cruz Chuqui, Martha Cecilia (2014)
This research has been developed in preliminaries and three chapters which are: specialized literature, methodology of the Ministry of Tourism (MINTUR), and to Develop a Didactic Guide of the el Boliche National Recreation Area; through the programming of graphic design for the knowledge and performance of students in the Tourism Interpretation Laboratory of Engineering Degree in Ecotourism, based on fieldwork, which allowed to fulfill the goals, becoming an educational multimedia program giving the facility of knowing attractives, physical and biological aspects, routes of the Boliche National Recreational Area through information, photos and interactive videos.